An International Cooperative Model of Online Chinese Courses. (March 2014) - Hsin, Shih-Chang; Wang, Ching-Wei; Huang, Yu-Hui
Abstract : This research project attempts to build a new cooperative model with the superintendents of school districts of various states in the United States. The idea behind the project is based on the urgent need of Mandarin Chinese courses in middle school level in the US. Since most school districts encounter the problem of not having enough Chinese teachers or teaching resources, offering Chinese courses through internet videoconferencing from Taiwan could be a feasible solution. This project involved some aspects including teaching materials design specifically for online instruction, communication with schools and their teachers/students, teacher's training for synchronized online instruction, e-learning platform and facilities arrangement, and problem solving along the implementation process. The program has been implemented during the year of 2012. We have cooperative agreements with five schools districts in different states and have established a workable operation model for this international cooperation. Through this cooperative model, American students gain the benefit of learning resources through internet, and Mandarin educators and researchers in Taiwan also gain new insights on how to promote the Chinese language learning in the global community.